Análise interseccional do perfil do professorado de física do ensino médio na Paraíba e no Brasil - Xavier, Maria Kamylla e Silva (2023)
This doctoral research aims to analyze the profile of current high school physics teachers in Brazil, considering intersectional aspects, highlighting those employed by the state of Paraiba, in Northeastern Brazil. To describe the national scenario, it uses microdata from the 2020 Basic Education Census (in the format made available by INEP until February 2022), treated by the R programming environment. To describe Paraiba’s scenario, in addition to INEP’s microdata, a questionnaire was administered to state schools’ physics teachers. The theoretical framework, based on Cultural Studies of Education and Science, as well as on Gender and Intersectionality Studies, seeks to articulate contributions from these fields to analyze the profile of physics teachers. The analysis uses descriptive statistics and multivariate data analysis, discussed in the light of intersectionality. The results indicate a predominant type or profile among high school physics teachers in Brazil: male, white, working in temporary contracts in the state’s public schools. Only 24.1% have a degree in Physics. Within Paraiba, the scenario is the same and presents much higher sex/gender inequality when compared to the national average; and, although the number of black people is greater, blacks, especially women, are more under-represented than at the national level. Methodologically, the articulation of macro and micro approaches can help to understand the gender, race, and class inequality that limits the advancement of women in physics, particularly as high school teachers. The results can contribute to teacher training policies and actions to stimulate the entry and permanence of women in physics and physics teaching.